ANALYSIS OF THE POLICY EFFECTIVENESS OF CORN TO RICE IN NORTHEAST CHINA - Luan Wang; Junnan Ding; Dingchen Zhang; Jing Zhang; Chunmiao Liu (Journal of Animal and Plant Sciences, 2026)
The income gap brought about by the cultivation of corn and rice has been widening, driving a structural adjustment in Northeast China from growing corn to growing rice. This paper uses household survey data from 2016 to 2018 and a Difference-in-Differences (DID) model to assess the impact of this structural adjustment on farmers’ agricultural income. The research results have identified three key findings. Farmers participating in the rice-growing transformation project have seen a significant increase in their income, and the productivity of their land has also improved. However, population factors can limit these benefits. For every year older a farmer is, their agricultural income decreases by 0.4%. This is because rice cultivation requires a relatively high labor intensity. Male-headed households earn 16.5% more than female-headed households. Most farmers in Northeast China earn money through agriculture, and their income is still easily affected by fluctuations in market prices. Based on these findings, this article believes that the government can continue to maintain the policy of price support and provide more technical services to help those elderly and weak labor force farmers.
Keywords: Corn-to-rice conversion; Difference-in-differences (DID); Farmer income; Structural adjustment; Northeast China